2022
DOI: 10.1136/gutjnl-2021-325373
|View full text |Cite
|
Sign up to set email alerts
|

A novel unconventional T cell population enriched in Crohn’s disease

Abstract: ObjectiveOne of the current hypotheses to explain the proinflammatory immune response in IBD is a dysregulated T cell reaction to yet unknown intestinal antigens. As such, it may be possible to identify disease-associated T cell clonotypes by analysing the peripheral and intestinal T-cell receptor (TCR) repertoire of patients with IBD and controls.DesignWe performed bulk TCR repertoire profiling of both the TCR alpha and beta chains using high-throughput sequencing in peripheral blood samples of a total of 244… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Only significant p values from a t-test with Holm method for multiple testing correction are shown (*<0.05, **<0.01, ***<0.001, ****<0.0001). (G.) Frequency of CAITlike NKT type II TCRs from Almeida et al (attached to a large cluster on figure 1A) and non-CAIT like NKT type II TCRs in Crohn’s disease and healthy cohorts from Rosati et al 1. Only significant p value (****<0.0001) from a Mann-Whitney U-test is shown.…”
Section: Mainmentioning
confidence: 97%
See 1 more Smart Citation
“…Only significant p values from a t-test with Holm method for multiple testing correction are shown (*<0.05, **<0.01, ***<0.001, ****<0.0001). (G.) Frequency of CAITlike NKT type II TCRs from Almeida et al (attached to a large cluster on figure 1A) and non-CAIT like NKT type II TCRs in Crohn’s disease and healthy cohorts from Rosati et al 1. Only significant p value (****<0.0001) from a Mann-Whitney U-test is shown.…”
Section: Mainmentioning
confidence: 97%
“…To further investigate the possible role of NKT type II cells in CD, we searched all NKT type II sequences reported in Almeida et al in our previously published TCR data from patients with CD and healthy controls 1 3. Only TCRs from NKT type II cells with the characteristic CAIT TCRalpha chain motif showed significant enrichment in patients with CD, while other TCRs were found in comparable amounts in patients and controls (figure 1G).…”
Section: Mainmentioning
confidence: 99%
“…The pattern and dynamics of these individual immune cells in liver fibrosis contribute to elucidating the protective mechanism of TCR in the chronic liver injury response ( 36 ). The TCRα chain is significantly enriched in the blood of patients with Crohn’s disease (CD), particularly in CD8+ T cell populations, whereas the potential effects of Crohn’s associated invariant T-cell subpopulations on CD remains to be elucidated ( 37 ). A total of 1650 glutamic acid decarboxylase 65-kilodalton isoform (GAD65)-specific CD4(+) T cells were isolated and 1003 different TCRs were identified in the peripheral blood of 6 patients and 10 patients with type 1 diabetes mellitus who were positive for islet autoantibodies.…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Theory supports unknown intestinal antigens could lead to dysregulated proinflammatory T‐cell immune responses. 8 However, it is unclear whether interactions between innate and adaptive immune cells within the gut are through microbe‐associated molecular pattern (MAMP) ‐ pattern recognition receptor (PRR) interactions, processing of intestinal antigens through MHC class II, or both. Investigations have reported that toll‐like receptor and MHC class II pathways can support one another due to similar processing of ligands/antigens within endosomal cellular compartments.…”
mentioning
confidence: 99%
“…Recognizing that GPR65 actions in epithelial cells, 6 macrophages, 7 and CD4 + T cells 5 contribute to the pathogenesis of IBD, this raises the question of whether innate immune cells regulate GPR65‐mediated T‐cell polarization towards proinflammatory T H 1 and T H 17 cells. Theory supports unknown intestinal antigens could lead to dysregulated proinflammatory T‐cell immune responses 8 . However, it is unclear whether interactions between innate and adaptive immune cells within the gut are through microbe‐associated molecular pattern (MAMP) ‐ pattern recognition receptor (PRR) interactions, processing of intestinal antigens through MHC class II, or both.…”
mentioning
confidence: 99%